Unrepresentable: Technological Futures, Art and The Ontological Singularity - O'DEA, TOM (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2019)
This thesis examines the implications of the increasing prevalence of computation in contemporary society. In doing so the thesis develops a definition of computation that is based on the manipulation and communication of abstract representations rather than specific technologies. As such this expanded definition allows the thinking of both human and machine practices as computational based on their relationship to abstraction. The thesis traces the route of this expanded definition of computation through the history of measurement practices to the present day in which abstraction in the form of data has become a dominant feature of contemporary society. The thesis examines the work of artists and theorists who have attempted to examine change in society brought about by computation. In doing so the thesis groups these attempts under three categorisations that relate to their specific focus rather than by disciplinary boundary. Thus the thesis highlights the need for a focus that crosses these areas of concerns and that pays attention to the abstract basis on which computation is built. By highlighting examples of abstract representation across contemporary society the thesis demonstrates the increasing dominance of abstraction as the primary site of engagement by individuals with the world and with each other. In this way the thesis shows how interaction with the abstract representations of computation gives rise to an increasing abstract construction of society. Through an examination of the functioning or representational systems and the interaction of memory and subjectivity the thesis proposes a mechanism by which this increasingly representational way of knowing is constantly reproduced. As such the thesis highlights the incompatibility of the abstract knowledge of computation with embodied and affective knowledges. Finally, the thesis suggests that art practice is a useful and necessary tool for understanding the implications of computation on contemporary society. Through an examination of the concept of multiplicity and in particular by highlighting the differences between discrete and continuous multiplicities the thesis suggests how art practice functions through the production of subjective knowledge that requires for its completion difference and individual subjectivity.
APPROVED
Keywords: Art; Computer Science; Representation; Computation; Measurment; Abstraction; Art Practice; Ontology; Ontological Singularity; Technology; STS; Feminist Epistemology; Cybernetics; Multiplicity; Subjectivity